Early administration of ivabradine in patients admitted for acute decompensated heart failure - Yang, Teng-Yao; Tsai, Meng-shu; Jan, Jeng-Yu; Chang, Jung-Jung; Chung, Chang-Ming; Lin, Ming-Shyan; Chen, Hui-Ming; Lin, Yu-Sheng (Frontiers in Cardiovascular Medicine, 2022)
Background Heart rate (HR) control is important in heart failure (HF) patients with reduced ejection fraction, and ivabradine is indicated for patients with chronic HF and sinus rhythm. However, ivabradine is limited in initiation of ivabradine at acute stage of HF. Methods This multi-institutional retrospective study enrolled 30,639 patients who were admitted for HF from 2013/01/01 to 2018/12/31 at Chang Gung Memorial Hospitals. After applying selection criteria, the eligible patients were divided into ivabradine and non-ivabradine groups according to the initiation of ivabradine at the index hospitalization. HR, clinical outcomes including HF hospitalization, all-cause hospitalization, mortality, the composite of cardiovascular (CV) death or HF hospitalization and newly developed atrial fibrillation, and left ventricular ejection fraction (LVEF) and left atrium size were compared between the ivabradine and non-ivabradine groups after inverse probability of treatment weighting (IPTW) analysis after 12 months. Results The HR at admission in the ivabradine group (n=433) was 99.04±20.69/min, compared to 86.99±20.34/min in the non-ivabradine group (n=9601). After IPTW, HR was lower in the ivabradine group than that in the non-ivabradine group after 12 months (74.14±8.53 vs. 81.23±16.79 bpm, p=0.079). However, there were no significant differences in HF hospitalization (HR=1.02; 95% CI, 0.38-2.79), all-cause hospitalization (HR=0.95; 95% CI, 0.54-1.68), mortality (HR=0.87; 95% CI, 0.69-1.08), the composite of CV death or HF hospitalization (HR=0.87; 95% CI, 0.69-1.08) and newly developed AF between the two groups. In addition, LVEF increased with time in both groups, but there were no significant differences during the observation period. Conclusions Ivabradine was beneficial in controlling HR when initiated in patients with acute stage of HF, but it did not seem to provide any benefits in reducing HF hospitalization, all-cause hospitalization and mortality in one year after discharge.